2017
DOI: 10.1016/j.jpeds.2017.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self-Assessed Sexual Maturation Against Physician Assessments and Hormone Levels

Abstract: Objective To compare self-report and physician assessments of sexual maturation against serum hormone markers to evaluate the hypothesis that the validity of self-assessed sexual maturation is underestimated in traditional validation studies. Study design We adapted a self-assessment instrument that 248 Mexican children and adolescents, age 8–13 years, completed. Participants were examined by a trained pediatrician and provided fasting blood samples for measurement of reproductive (testosterone, estradiol, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 68 publications
3
87
1
1
Order By: Relevance
“…Nonetheless, this research used a highly reliable protocol for assessing pubertal development based on instructions from the American Academy of Pediatrics Assessment of Sexual Maturity Stages in Girls (22). Moreover, it was recently confirmed that self-assessment can be validly used in evaluating sexual maturation in children (23). A second limitation is that assessments of the subjects in SECCYD were done until age 15.5 years.…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, this research used a highly reliable protocol for assessing pubertal development based on instructions from the American Academy of Pediatrics Assessment of Sexual Maturity Stages in Girls (22). Moreover, it was recently confirmed that self-assessment can be validly used in evaluating sexual maturation in children (23). A second limitation is that assessments of the subjects in SECCYD were done until age 15.5 years.…”
Section: Discussionmentioning
confidence: 94%
“…Two pediatricians (CB-G and AM-G), trained according to standard methods (Chavarro et al 2017), evaluated Tanner staging in female offspring using standardized protocols. We used breast developmental stage (BD) as an indicator of puberty and pubic hair stage (PH) as an indicator of adrenarche, with stage 1 corresponding to no development and stage 5 corresponding to full development (Marshall and Tanner 1969).…”
Section: Methodsmentioning
confidence: 99%
“…Pubertal development was measured using physician-assessed Tanner staging, ranging from 1 (no development [preteen]) to 5 (mature stage [adult]). [50][51][52] Consistent with prior research, 53 we used the average Tanner score for physician-observed pubic hair development and breast development to measure pubertal development in girls and the average Tanner score for physician-observed pubic hair development and genital development to measure pubertal development in boys.…”
Section: Methodsmentioning
confidence: 99%